2005
DOI: 10.1016/j.neuroimage.2005.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume reduction in the chronic fatigue syndrome

Abstract: The chronic fatigue syndrome (CFS) is a disabling disorder of unknown etiology. The symptomatology of CFS (central fatigue, impaired concentration, attention and memory) suggests that this disorder could be related to alterations at the level of the central nervous system. In this study, we have used an automated and unbiased morphometric technique to test whether CFS patients display structural cerebral abnormalities. We mapped structural cerebral morphology and volume in two cohorts of CFS patients (in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
118
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 27 publications
8
118
1
Order By: Relevance
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 84%
“…One study found a decrease in regional GM volume in prefrontal areas,7 and another found such decreases in the occipital lobe, right angular gyrus, and left parahippocampal gyrus 12. Cortical thickness was found to be increased in right arcuate fasciculus end points, the middle temporal gyrus, precentral gyri, and occipital lobe,8 while other studies did not find significant regional GM differences 6, 11. Similarly, inconsistent WM changes have been reported 8, 11, 12, 13.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, an overlap exists in components of the pain neuromatrix and brain regions involved in cognitive processing (e.g., anterior cingulate cortex, insular cortex, periaqueductal gray) (14). Together with the demonstrated changes in neuroplasticity [e.g., gray matter volume reduction (15)(16)(17)] and dysregultated neurochemistry [e.g., decreased levels of brain-derived neurotrophic factor (18), increased levels of gamma-aminobutric acid (19), increased levels of pro-inflammatory cytokines (20)], these pain-induced changes in resource utilization may (in part) explain (pain-related) cognitive impairment in chronic pain patients.…”
Section: Participants and Assessmentsmentioning
confidence: 99%